ANALISIS JABATAN STRUKTURAL PADA SEKRETARIAT DAERAH KABUPATEN BENGKALIS - Yoga, Ardina Eka; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Job analysis has a very important role in Human Resource Management for achieving the organization main goal. From the analysis of these positions then the organization will be able to determine characteristics such as what should be owned by prospective employees before taking a position, the output in the form job spesification and descriptions. This research was conducted at the district Secretariat Bengkalis in order to determine how the analysis of the structural position in Bengkalis district Secretariat and to determine the factors that become obstacles in the analysis positions at the district Secretariat Bengkalis. This study uses theory Moekijat (2010) with qualitative research methods. In conducting the data collection data collection techniques used observation and interview to the informant research. After the data is collected and the conclusions drawn and analyzed using descriptive qualitative data analysis techniques. The conclusion of this research is the analysis of structural positions at the district Secretariat Bengkalis been good, but there are some things that have not been implemented optimally. In the job spesification, there are the employees who are placed in areas that do not correspond with the educational background and to the position description is also already well as good working conditions. Constraints faced by the Secretariat of the district Bengkalis in job analysis lack the skills and capabilities of the employess in accordance with the position they occupy causes the task that can not be resolved properly and experience related to the position hel by the employees is nit fully associated with the position they occupy now. The author suggested to the district Secretariat Bengkalis order in Human Resorces planning by hail job analysis so that the formation of professional personnel in carrying out their duties.Keywords: job analysis, job spesification, job description